Pendampingan Edukasi Pemasaran Komunitas Pengusaha Keripik Gadung Berbasis Digital Marketing dan E-Commerce Desa Begagan Limo Kecamatan Gondang Mojokerto - Ummah, Nahdiyatul; Ubaidillah, M. Hasan; Umayyah, Ummu (Fakultas Ekonomi Universitas Islam Majapahit, 2025)
The educational support program for digital marketing and e-commerce for the community of gadung chips entrepreneurs in Bagagan Limo Village, Gondang District, Mojokerto aims to enhance their marketing capabilities to reach a broader and more efficient market. This program provides entrepreneurs with an understanding of basic digital marketing concepts, ranging from social media utilization to e-commerce platforms, to expand their market reach. The assistance is carried out through training and hands-on practice, allowing participants to implement the knowledge gained in marketing their products online. The education provided covers various aspects of digital marketing, such as social media content management, website optimization, and the use of e-commerce platforms for product sales. This is intended to help gadung chips entrepreneurs not only rely on the local market but also penetrate broader markets, including international markets, through digital platforms. Furthermore, the support program teaches effective and cost-efficient marketing techniques, considering the importance of leveraging digital media in the modern era. Through this program, it is expected that gadung chips entrepreneurs in Bagagan Limo Village can develop their businesses, increase their income, and create new business opportunities. The implementation of digital marketing and e-commerce is expected to have a positive impact on improving the competitiveness of gadung chips products, as well as introducing local products to the global market. The desired outcome is the creation of a more inclusive and sustainable business ecosystem in the village.